Childhood abuse and neglect are prospectively associated with scripted attachment representations in young adulthood. (October 2021) - Nivison, Marissa D.; Facompré, Christopher R.; Raby, K. Lee; Simpson, Jeffry A.; Roisman, Glenn I.; Waters, Theodore E. A.
Abstract: Waters, Ruiz, and Roisman (2017) recently published evidence based on the Minnesota Longitudinal Study of Risk and Adaptation (MLSRA) that sensitive caregiving during childhood is associated with higher levels of secure base script knowledge during the Adult Attachment Interview (AAIsbs ). At present, however, little is known about the role of variation in atypical caregiving, including abuse and/or neglect, in explaining individual differences in AAIsbs . This study revisited data from the MLSRA ( N = 157) to examine the association between experiencing abuse and/or neglect in the first 17.5 years of life and secure base script knowledge measured at ages 19 and 26 years. Several aspects of abuse and/or neglect experiences were assessed, including perpetrator identity, timing, and type. Regressions revealed that childhood abuse and/or neglect was robustly associated with lower AAIsbs scores in young adulthood, above and beyond previously documented associations with maternal sensitivity and demographic covariates. Follow-up analyses provided evidence that the predictive significance of abuse for secure base script knowledge was specific to perpetration by parental figures, rather than non-caregivers. Exploratory analyses indicated that abuse and/or neglect: (a) in middle childhood and adolescence (but not infancy and early childhood) and (b) physical abuse (but not sexual abuse or neglect) were uniquely associated with lower AAIsbs scores.